2017
DOI: 10.1073/pnas.1615792114
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a is essential for hippocampal dendritic maintenance and spatial learning and memory in adult mice

Abstract: Stability of neuronal connectivity is critical for brain functions, and morphological perturbations are associated with neurodegenerative disorders. However, how neuronal morphology is maintained in the adult brain remains poorly understood. Here, we identify Wnt5a, a member of the Wnt family of secreted morphogens, as an essential factor in maintaining dendritic architecture in the adult hippocampus and for related cognitive functions in mice. Wnt5a expression in hippocampal neurons begins postnatally, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 96 publications
1
63
0
Order By: Relevance
“…It was previously shown that Wnt ligands that signal through the canonical Wnt/β‐catenin pathway regulate proliferation and fate commitment of NPCs; however, the role of noncanonical Wnt ligands on adult neurogenesis has been less explored. Here, we investigated the role of Wnt5a, which is expressed in the adult hippocampus and in AHPs, and it is known to activate noncanonical Wnt/JNK and Wnt/Ca +2 signaling pathways in cultured hippocampal neurons, and Wnt/JNK signaling in differentiating AHPs . We determined that genetic knockdown of Wnt5a in the dentate gyrus decreased the generation of adult‐born neurons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was previously shown that Wnt ligands that signal through the canonical Wnt/β‐catenin pathway regulate proliferation and fate commitment of NPCs; however, the role of noncanonical Wnt ligands on adult neurogenesis has been less explored. Here, we investigated the role of Wnt5a, which is expressed in the adult hippocampus and in AHPs, and it is known to activate noncanonical Wnt/JNK and Wnt/Ca +2 signaling pathways in cultured hippocampal neurons, and Wnt/JNK signaling in differentiating AHPs . We determined that genetic knockdown of Wnt5a in the dentate gyrus decreased the generation of adult‐born neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have involved CaMKII in activity‐dependent dendrite development of cultured hippocampal neurons, and in Wnt7b‐induced dendritogenesis in cultured pyramidal neurons . In addition, CaMKII is involved in Wnt5a‐dependent maintenance of dendritic arborization in CA1 pyramidal neurons of the adult hippocampus . Therefore, it is likely that in the adult dentate gyrus, Wnt5a signals through the Wnt/CAMKII pathway to regulate morphogenesis of adult‐born neuron.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations